(untitled) (London Journal of Engineering Research, 2024)
Paraffin scale deposition poses a significant challenge in various industries, including oil and gas production, where it leads to reduced operational efficiency and increased maintenance costs. This study focuses on the utilization of off-the-shelf household candle wax to simulate typical oilfield paraffin scale deposits and, simultaneously, to characterize them in order to gain deeper insights into their chemical, and compositional properties in relation to typical oilfield paraffin scale deposits. Controlled laboratory experiments were conducted to mimic paraffin scale deposition under conditions resembling those encountered in production systems. The deposition process was monitored and chemically characterized using advanced analytical techniques, such as Fourier-transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) spectroscopy. This analysis provided valuable information about the molecular composition of the deposits, including the types of paraffin involved and the presence of other organic and inorganic compounds. In conclusion, mimicking and characterizing the simulated paraffin scale deposits provide valuable insights into their behaviour and composition, shedding light on factors influencing paraffin deposition preservation. This knowledge is critical for the development of tailored solutions to mitigate or remove paraffin scale-related challenges, ultimately leading to improved operational efficiency and reduced economic impact across various industries.